Effect of ICT on students achievements and motivation in life and earth sciences subject - Janous, Youssra; El-Hassouny, Hassan; Laafou, Mohamed; Madrane, Mourad (Pegem Journal of Education and Instruction, 2022)
As contemporary society evolves, technological revolutions are increasingly forcing academic and secondary institutions to adopt innovative strategies rather than traditional instruction. Improving the teaching of life and earth sciences will enhance student success. Therefore, the use of ICT in teaching is an active teaching method with proven effectiveness on learning outcomes and student motivation in life and earth sciences. Our study for the 2020/2021 academic year was a quantitative experimental pilot study to examine the impact of ICT integration on student learning and motivational outcomes in science education. Third year middle school students We used three tests, the knowledge test, the achievement of objectives test and the motivation test. The control group consisted of 30 students compared with 30 students in the experimental group, and the experiment lasted 8 weeks. The results obtained showed a very particular statistical increase (p<0.0001) in the results and the degree of motivation of the students in the experimental group. According to our results, the integration of ICTE could be an effective way to improve students’ learning and increase their motivation for teaching life and earth sciences.